Development of a novel HVDC system model for control design - Pandey R.K.; Ghosh A.; Sachchidanand (My University, 2025)
The operation of HVDC converters is discrete in nature. It is, therefore, proper to take into account the discrete behavior of converter operation while developing the system model for small signal stability analysis. This paper presents the development of such a system model, which also explicitly includes the effect of phase angle of respective AC bus voltages. A modular approach has been adopted for the formulation of complete state space system model. Utilizing the system model, the stability is examined in the controller parameter plane using eigenvalue analysis. The stability domains thus obtained are validated through detailed dynamic digital simulation. © 1999, Taylor & Francis Group, LLC. All rights reserved.